Plaque quantification by coronary computed tomography angiography using intravascular ultrasound as a reference standard: a comparison between standard and last generation computed tomography scanners. (15th May 2019) - Conte, Edoardo; Mushtaq, Saima; Pontone, Gianluca; Li Piani, Letizia; Ravagnani, Paolo; Galli, Stefano; Collet, Carlos; Sonck, Jeroen; Di Odoardo, Luca; Guglielmo, Marco; Baggiano, Andrea; Trabattoni, Daniela; et al.
Abstract: Aims: The emerging role of coronary computed tomography angiography (CCTA) as a non-invasive tool for atherosclerosis evaluation is supported by data reporting a good correlation between CCTA and intravascular ultrasound (IVUS) for plaque volume quantification. Aim of the present study was to evaluate whether a last generation CT-scanner may improve coronary plaque volume assessment using IVUS as standard-of-reference. Methods and results: From a registry of 1915 consecutive, all-comers, patients who underwent a clinically indicated IVUS evaluation we enrolled 59 patients who underwent CCTA with a 64-slice CT (Group 1) and 59 patients who underwent CCTA with whole-heart coverage CT scanner (Group 2). Patients who underwent CCTA with unfavourable heart rhythm were not excluded from the analysis. Image quality (4-point Likert scale) focused on plaque analysis was evaluated. Plaque volume quantification by CCTA was compared to IVUS. No difference in clinical characteristics was found between Group 1 and Group 2. Plaque volume quantification by CCTA was considered not feasible in 11 plaques of Group 1 and in 4 plaques of Group 2 ( P  = 0.09). Higher correlation for plaque volume quantification by CCTA vs. IVUS was demonstrated in Group 2 when compared with Group 1 ( r  = 0.9888 vs. 0.9499; P  < 0.0001). The Bland–Altman analysis showed plaque volume overestimation by CCTA of 11.9 mm 3 in Group 1 and 4 mm 2 in Group 2 ( P  < 0.001). Effective radiation dose of CCTA was significantly lower in Group 2 vs. Group 1 (2.7 ± 0.9 vs. 8.1 ± 3.6 mSv, respectively; P  < 0.001). Conclusions: CCTA using a new scanner generation showed to be an accurate non-invasive tool to assess and quantify coronary plaque volume.